Vibration Characteristic Analysis of Shearer Cutting Unit and the Transmission System Structure Optimization - Zhao Lijuan; Chen Peng; Song Peng (Jixie chuandong)
A virtual rigid-flex coupled prototyping of a new type shearer cutting unit is established based on the software of Pro/ENGINEER,ADAMS,ANSYS and MATLAB,and the forced vibration analysis of shearer cutting unit model is carried out based on the ADAMS/Vibration module,through the observation of main vibration mode of system find out that cutting of the excitation system does not inspire cutting part resonance occurs,but observation the system 33 order vibration mode,found near the center of mass in the shearer cutting,a larger torsional vibration is occuring,in order to improve the stability of coal winning machine shearer cutting,its transmission system is optimized,the results show that the centroid of the optimized shearer cutting x,y,zthree directions of the acceleration response amplitude is reduced by 74.2%,64.83% and 7.02%respectively,the torsional vibration decrease obviously,other test points are also significantly reduce the vibration amplitude,and the free modal and constraint modal of shell deformation amplitude have been improved significantly,decreased by 95.9% and 93.98% respectively,the optimization effect is remarkable.